Long-Term in vivo Impedance Changes of Subretinal Microelectrodes Implanted in Dystrophic P23H Rats. Issue 9 (September 2013) - Linderholm, Pontus; Guyomard, Jean-Laurent; Djilas, Milan; Salzmann, Joël; Simonutti, Manuel; Sahel, José A.; Safran, Avinoam B.; Renaud, Philippe; Picaud, Serge
Retinal prostheses are being developed to restore vision in blind patients with photoreceptor degeneration. Electrodes arrays were subretinally implanted in transgenic P23H rats with their photoreceptors degenerated. Electrical stability of the implants was evaluated by long-term monitoring of their impedance changes. Electrode impedances were found to increase by two log units over a three weeks period whereas no impedance increase was noted when the implants were located in the vitreous. In case of hemorrhage or major fibrous reactions, the impedance continued to increase steadily. After explantation, it recovered its initial value indicating no deterioration of the implant. Although the glial cell layer at the surface of the subretinal space was slightly larger, no major glial reaction was seen in direct contact to the implant. These results indicate that no functional testing should be considered before at least three weeks post implantation.